Performance Test of Vegetative Characteristics of Pigmented Local Rice at Various Levels of Soil Water Content - Nur Fauziah, Qori; Purwanto, Edi; Rahayu, Muji (Universitas Panji Sakti, 2025)
The conversion of land to dry land promotes the use of local rice varieties capable of withstanding drought conditions, thus contributing to the development of sustainable agricultural practices. The anthocyanin content of pigmented rice may confer a greater resilience to cell damage caused by drought conditions than white rice. This study aims to evaluate the vegetative characteristics of local pigmented rice at varying soil water content levels. The study was conducted from June to August 2024 at the Agricultural Laboratory of Sebelas Maret University. Eight rice varieties were utilized, including two control rice varieties, two local white rice varieties, and four local pigmented rice varieties. The experimental design was a completely randomized block design split plot with three blocks and two factorials: eight rice varieties and four levels of soil water content. Data analysis was conducted using the ANOVA, Duncan, and regression tests. The findings indicated that Hitam Cempo and Merah Wangi exhibited optimal growth at a lower soil water content of field capacity (25% FC) than white rice and IR64 control. Hitam Mutiara and Merah Wangi exhibited optimal responses at 75% and 50% FC, respectively, compared to the white rice and IR64 control varieties. Leaf rolling scores increased in black and red rice as soil water content decreased compared to white rice. The research findings indicate that, based on the vegetative characteristics of local pigmented rice, it has the potential to be more drought tolerant than white rice. Further research on testing physiological and biochemical resistance traits is needed to support the development of rice types that can be planted in dry land.